Primary Systemic Anaplastic Large Cell Lymphoma in Korean Adults: 11 Years' Experience at Asan Medical Center - Park, Soo Jung; Kim, Shin; Lee, Dae Ho; Jeong, Yong Pil; Bae, Yunjeong; Han, Eun Mee; Huh, Jooryung; Suh, Cheolwon (Yonsei medical journal, 2008)
Anaplastic large cell lymphoma (ALCL), a CD30+ T-cell non-Hodgkin's lymphoma, represents only 2-8% of lymphoma overall. Information on the clinical findings of primary systemic ALCL in Korea is limited. Our aims were to report the clinical features and outcomes of primary systemic ALCL. We retrospectively reviewed the medical records of 36 adult patients diagnosed with primary systemic ALCL at Asan Medical Center from February 1995 through June 2006. Of 36 patients, 29 were male. The median age was 39 years (range, 17-67 years), and 26 (72%) presented with Ann Arbor stages III and IV. The most commonly involved extranodal sites were bone (n = 7) and soft tissue (n = 6). Thirty-two of all patients (89%) were treated with an anthracycline-based regimen including cyclophosphamide/doxorubicin/vincristine/prednisone (CHOP) as induction chemotherapy; 16 (50%) achieved complete remission (CR), and 13 (41%) achieved partial remission (PR). Median overall survival (OS) and event-free survival (EFS) were 49 and 17 months, respectively. Univariate analysis showed that performance status (p = 0.035), international prognostic index (IPI) (p = 0.025), and age-adjusted IPI (p = 0.034) were significant prognostic factors for OS, whereas anaplastic lymphoma kinase (ALK) expression did not affect OS (p = 0.483). Our retrospective analysis of Korean primary systemic ALCL patients showed that median OS was 49 months and overall response to CHOP was 91%. Performance, IPI, and age-adjusted IPI were predictors of OS, whereas ALK expression did not have prognostic significance.